(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
During the Soviet years a well-established unified settlement network had been formed in the Republic of Armenia (RA), with a multilevel settlement system and equalization trends. However, the landmark events that occurred in the last years of the Soviet period, as well as the geopolitical and socio-economic conditions shaped after gaining independence have initiated a powerful wave of emigration, a demographic crisis and, as a result, depopulation of the country. Under the conditions of the new realities, the settlement pattern of the RA has undergone significant transformations. The article is dedicated to the study of its specifics, trends, problems, as well as territorial differences. The research revealed that the problems of depopulation, migration and the demographic crisis have different manifestations and transformations in different types of settlements and territorial zones of Armenia.Vulnerable territories of the RA (mountainous and high-altitude areas, territories with unfavorable natural-geographical and socio-economic conditions, with problems related to border security and life support, territories outside the zones of influence of the settlement system) react more acutely to negative and undesirable processes, resulting even to total depopulation. At the same time, a number of settlement areas in Armenia with competitive comparative advantages are becoming to hubs of population growth and economic development, rather than depopulation centers. As a result of the ongoing processes, there is a sharp polarization of the settlement patterns in the RA. It has become an existential problem and requires comprehensive solutions in regional policy.